A highly selective fluorescent chemosensor for Mg2+ based on a diarylethene with a quinoxaline unit. (29th November 2019) - Zhang, Yaping; Li, Hui; Jiang, Duohua; Pu, Shouzhi
Abstract: A new fluorescent probe 1O was synthesized through linking diarylethene and Quinoxaline‐2‐hydraqzide group, probe 1O showed a selective "off‐on" fluorescent response toward Mg 2+ . In the presence of Mg 2+, the probe 1 O displayed a distinct change of fluorescence color, from dark to green, the fluorescence intensity increased 6.8‐fold, and meanwhile, emission peak has a significant blue shift, which was shifted from 524 nm to 518 nm. Then, on account of the fluorescence properties of compound 1O, we designed a logic gate. On top of that, probe 1O also can be successfully used to monitor Mg 2+ of the actual water samples. Abstract : A new photochromic diarylethene derivative, based on Quinoxaline‐2‐hydraqzide group, was synthesized; it can be used to recognize Mg 2+ . The diarylethene derivative could be applied to the design of molecular logic circuit and detect Mg 2+ in natural water samples with high accuracy.